Biomechanical and histologic evaluation of two application forms of surgical glue for mesh fixation to the abdominal wall. (November 2017) - Ortillés, Á.; Pascual, G.; Peña, E.; Rodríguez, M.; Pérez-Köhler, B.; Mesa-Ciller, C.; Calvo, B.; Bellón, J.M.
Abstract: The use of an adhesive for mesh fixation in hernia repair reduces chronic pain and minimizes tissue damage in the patient. This study was designed to assess the adhesive properties of a medium-chain (n-butyl) cyanoacrylate glue applied as drops or as a spray in a biomechanical and histologic study. Both forms of glue application were compared to the use of simple-loose or continuous-running polypropylene sutures for mesh fixation. Eighteen adult New Zealand White rabbits were used. For mechanical tests in an ex vivo and in vivo study, patches of polypropylene mesh were fixed to an excised fragment of healthy abdominal tissue or used to repair a partial abdominal wall defect in the rabbit respectively. Depending on the fixation method used, four groups of 12 implants each or 10 implants each respectively for the ex vivo and in vivo studies were established: Glue-Drops, Glue-Spray, Suture-Simple and Suture-Continuous. Biomechanical resistance in the ex vivo implants was tested five minutes after mesh fixation. In vivo implants for biomechanical and histologic assessment were collected at 14 days postimplant. In the ex vivo study, the continuous suture implants showed the highest failure sample tension, while the implants fixed with glue showed lower failure sample tension values. However, the simple and continuous suture implants returned the highest stretch values. In the in vivo implants, failure sample tension values were similar among groups while the implants fixed with a continuous running suture had the higher stretch values, and the glue-fixed implants the lower stretch values. All meshes showed good tissue integration within the host tissue regardless of the fixation method used. Our histologic study revealed the generation of a denser, more mature repair tissue when the cyanoacrylate glue was applied as a spray rather than as drops.